2017
DOI: 10.1016/j.diabres.2017.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Depressive states among adults with diabetes: Findings from the National Health and Nutrition Examination Survey, 2007–2012

Abstract: Aims To determine (1) the prevalence of SubD states among adults with diabetes, and (2) whether evidence exists of an independent association between diabetes status and SubD, controlling for selected confounders. Methods Data from the 2007–2012 National Health and Nutrition Examination Surveys were combined to estimates of depressive states by diabetes status among the noninstitutionalized U.S. adult population, and to assess the association of diabetes status and depressive states using a polytomous logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
(63 reference statements)
1
13
0
Order By: Relevance
“…Overall prevalence was 0.3% (95% CI: 0.1–0.7%). Based on the five included studies [ 55 , 56 , 57 , 58 , 59 ], the unadjusted pooled odds ratio was 1.85 (95% CI: 0.97–3.52, p -value = 0.061) ( Figure 2 ), with significant heterogeneity ( I 2 = 94.79%, Q = 76.88, p -value < 0.001). Adjusted OR (based on three studies) was 1.39 (95% CI: 0.82–2.35, p -value= 0.225) ( I 2 = 81.66%, Q = 10.90, p -value = 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…Overall prevalence was 0.3% (95% CI: 0.1–0.7%). Based on the five included studies [ 55 , 56 , 57 , 58 , 59 ], the unadjusted pooled odds ratio was 1.85 (95% CI: 0.97–3.52, p -value = 0.061) ( Figure 2 ), with significant heterogeneity ( I 2 = 94.79%, Q = 76.88, p -value < 0.001). Adjusted OR (based on three studies) was 1.39 (95% CI: 0.82–2.35, p -value= 0.225) ( I 2 = 81.66%, Q = 10.90, p -value = 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Depression is present in about one in five adults with type 2 diabetes. [5][6][7] Diabetes distress affects almost one third of adults with type 2 diabetes. 3 Diabetes distress is distinct from depression, as it results from the emotional burden (e.g., worry, frustration, anger, burnout) of managing type 2 diabetes.…”
mentioning
confidence: 99%
“…In some studies of people with T2D, the prevalence of subthreshold depression has been reported to be more common than MDD [20][21][22]. Like major depression, subthreshold depression is also associated with a higher rate of diabetes-related complications [11,13], disability [11], and mortality [11,23,24].…”
Section: Introductionmentioning
confidence: 99%